Pengaruh Konseling Kelompok Teknik Cognitive Restructuring untuk Mengatasi Perilaku Celebrity Worship Kpop pada Siswa Kelas X SMK Negeri 1 Kuantan Mudik (International Forum of Researchers and Lecturers, 2025)
“Hallyu” (the Korean Wave) refers to the popularity of everything originating from Korea. Aims to examine the description of students’ K-Pop celebrity worship behavior before and after receiving group counseling with the Cognitive Restructuring technique, analyze the differences in students’ behavior, and test the effect of the counseling on reducing celebrity worship tendencies. The findings are expected to provide theoretical contributions to the field of guidance and counseling, particularly regarding the application of Cognitive Restructuring to mitigate obsessive behaviors, as well as practical benefits for school counselors and institutions in helping students reduce celebrity worship tendencies so they can remain focused on academic and social development. The research employed an experimental method with a One-Group Pretest–Posttest design. The subjects consisted of eight tenth-grade students at SMK Negeri 1 Kuantan Mudik who were identified as having a high level of K-Pop celebrity worship. The instrument used was a 19-item K-Pop celebrity worship scale that had been tested for validity and reliability. Data were analyzed using the Wilcoxon test and N-Gain calculations to determine treatment effectiveness. The results showed that prior to receiving group counseling with Cognitive Restructuring techniques, most students were categorized as having high or moderate levels of celebrity worship. After the intervention, all students experienced a decrease in celebrity worship behavior, falling into the low category. This demonstrates that group counseling using Cognitive Restructuring is effective in helping students shift irrational thinking patterns toward more rational ones, enabling them to control excessive celebrity worship behavior.